FROM CEREMONY TO RESPONSIBILITY: OATH OF OFFICE AS AMANAH IN THE MINISTRY OF RELIGIOUS AFFAIRS - Gasim Yamani; Fatimawali Fatimawali (Tadayun: Jurnal Hukum Ekonomi Syariah, 2025)
This study examines the effectiveness of the oath of office within the bureaucracy of the Ministry of Religious Affairs of Central Sulawesi and reconstructs its meaning as an entrusted responsibility (amanah) with legal, ethical, and social consequences. Employing a socio-legal approach, this research analyzes the oath of office not only as a normative legal requirement but also as a living legal norm operating within bureaucratic practices. Data were collected through in-depth interviews with civil servants, observation of oath-taking ceremonies, and document analysis. The findings reveal a significant gap between legal norms and bureaucratic practices, where the oath of office is predominantly perceived as a formal and ceremonial procedure rather than a continuous ethical commitment. From the perspective of legal effectiveness theory, this condition reflects weaknesses in legal culture, organizational environment, and enforcement mechanisms rather than deficiencies in legal substance. Furthermore, this study conceptualizes the oath of office as a form of public trust that aligns with the fiduciary relationship doctrine in modern law and the Islamic concept of amanah. The research contributes theoretically by integrating socio-legal analysis with Islamic legal ethics and practically by offering a reconstruction of the oath of office to strengthen bureaucratic integrity, accountability, and ethical governance. Abstrak Penelitian ini mengkaji efektivitas sumpah jabatan dalam birokrasi Kementerian Agama Provinsi Sulawesi Tengah serta merekonstruksi pemaknaannya sebagai amanah yang melahirkan konsekuensi hukum, etika, dan sosial. Penelitian ini menggunakan pendekatan sosiologis hukum untuk menganalisis sumpah jabatan tidak hanya sebagai norma hukum formal, tetapi juga sebagai hukum yang bekerja dalam praktik birokrasi. Data diperoleh melalui wawancara mendalam dengan aparatur sipil negara, observasi prosesi sumpah jabatan, dan studi dokumen. Hasil penelitian menunjukkan adanya kesenjangan antara norma hukum dan praktik birokrasi, di mana sumpah jabatan cenderung dipahami sebagai prosedur seremonial, bukan sebagai komitmen etis yang berkelanjutan. Dalam perspektif teori efektivitas hukum, kondisi ini lebih disebabkan oleh lemahnya budaya hukum, lingkungan organisasi, dan mekanisme penegakan, bukan oleh kekurangan substansi hukum. Penelitian ini juga menempatkan sumpah jabatan sebagai hubungan kepercayaan publik yang sejalan dengan doktrin fiduciary relationship dalam hukum modern dan konsep amanah dalam hukum Islam. Secara teoretis, penelitian ini memperkaya kajian hukum ekonomi syariah melalui integrasi analisis sosio-legal dan etika Islam, serta secara praktis menawarkan rekonstruksi sumpah jabatan untuk memperkuat integritas dan akuntabilitas birokrasi.